Preliminar studies on somaclonal variation of carnation (dianthus caryophyllus), and "in vitro" selection of calluses and plantlets resistants to fusarial wilt (1990)
Five experiments were carried outin the laboratory to obtain callus and plantlets from young petals of carnation(Dianthus caryophyilus) using differentconcentrations of BAP, NAA, 2,40 and light/dark treatments. The best results wereobtained with Murashige and Skoog madium containing 0,5 ppm of BAP, 2 ppm of NAA and O,1 ppm of 2,4D on light conditions. It was determinated that the whole petal asexplant was better to obtain plantlets regenerated. For the selection pressure it wasused autoclaved toxic material of F. oxysporum f. sp. dianthi (between O and 40%)mixad with the plantlets and callus regenerated medium. From this experiment it was obtained possible tolerants somaclonal variants of carnation to 10% level of toxics materials.